Root exudates in mangrove forests accelerate bicarbonate production in the soil environment - Norihiro Kato; Ken’ichi Osaka; Toshiyuki Ohtsuka; Yasuo Iimura (Scientific Reports)
Abstract Mangrove forests are increasingly recognized as vital blue carbon ecosystems due to their high carbon sequestration capacity, primarily through the accumulation of soil organic carbon (SOC). Recent research highlights that, in addition to SOC, dissolved inorganic carbon (DIC), particularly in the form of bicarbonate (HCO₃⁻), plays a crucial role in carbon sequestration by being exported from these ecosystems to adjacent coastal waters. This study aims to investigate the previously unexamined mechanisms behind bicarbonate production in mangrove soils. We test the hypothesis that root exudates, specifically sugars and organic acids, induce a priming effect that enhances DIC production. We conducted a month-long incubation experiment using soil samples from an estuarine mangrove forest in Japan, under varying salinity levels and root exudate treatments. During the incubation period, the total amounts of DIC, HCO₃⁻, and carbonic acid (H₂CO₃) detected per vial in each treatment ranged from 30.0 to 43.9 mg C, 26.6 to 39.7 mg C, and 1.9 to 4.4 mg C, respectively, with HCO₃⁻ accounting for approximately 90% of the DIC. These values tended to be higher under high salinity conditions resembling seawater levels. In particular, the treatment with a complex solution of root exudates and high salinity (h-ASW + c-REC) showed the highest average values for all forms of DIC. Furthermore, in the h-ASW + c-REC treatment, HCO₃⁻ increased significantly (P < 0.005) by approximately 20% compared to the control without added root exudates. Additionally, changes in water quality parameters—including increased NH₄⁺ levels and decreased dissolved oxygen and oxidation-reduction potential—provided further support for the priming effect hypothesis. This study is the first to demonstrate that root exudates promote bicarbonate production in mangrove soils, offering new insights into the complex carbon and nutrient dynamics in these ecosystems.